(untitled) (Research, Society and Development, 2020)
This paper aims to analyze the sanitation services of the rural community of Amadeu Lacerda in the municipality of Divinópolis, Minas Gerais, Brazil, from the perspective of the thematic categories of rural management and economic sustainability, addressing their aspects and particularities in discussion with the state of the art. The work presents itself as a qualitative and quantitative, exploratory and analytical research. Using the technique of field diary research and direct observation, a mapping and diagnosis of the existing systems and structures was performed. The analysis of the financial sustainability of the water supply system points to the inability to fund the necessary actions and to provide the service satisfactorily, interfering with issues such as installation and maintenance of treatment structures, water quality control and fund administration. reserve for possible expenditure. The management of the sanitation service of the community of Amadeu Lacerda is precarious in different aspects, from the point of view of operation, maintenance, logistics, as well as in human resources and system permanence, directly impacting the quality of life of the population. It is proposed as an alternative the adoption of the management model based on self-organization, which can contribute both to the improvement of the service as well as to the engagement and empowerment of community residents.